Chromium adsorption on banana rachis adsorbent from tannery wastewater : optimization, isotherm, kinetics and desorption studies - Payel, Sofia (Array, 2020)
This study investigates the banana rachis adsorbent for adsorption characterization, removal, and recovery of the chromium ion from the chrome tanning wastewater. The batch analysis was conducted to find out an adsorbent dose, contact time, relative pH of the aqueous solution, and initial and final chromium value in the filtrate. The equipped adsorbent was studied by the Fourier transform infrared spectroscopy (FT-IR) analysis to reveal the associated functional groups during adsorption. Batch adsorption examination reveals the optimum conditions of 3 g adsorbent input for 75 mL wastewater at 15 min contact time. The adsorption mechanism showed chromium removal 99.64% with the obtained reduction of biochemical oxygen demand (BOD), chemical oxygen demand (COD), and chloride (Cl-) 96.65%, 93.18%, and 59.62%, respectively. The adopted method followed the pseudo-second-order kinetics and Freundlich isotherm for physical adsorption. Primary desorption studies exhibit a scope for the reuse of chromium from the adsorbed adsorbent. Moreover, in comparison with other studies, the study discloses that banana rachis might be utilized as a feasible adsorbent to be adopted in industrial wastewater treatment, especially chrome tanning wastewater in the tannery.